Multi-Watt Near-Infrared Phototherapy for the Treatment of Comorbid Depression: An Open-Label Single-Arm Study - Henderson, Theodore A.; Morries, Larry D. (Frontiers in Psychiatry, 2017)
Background: Recent work demonstrated multi-Watt transcranial near-infrared light therapy (NILT) can effectively treat traumatic brain injury (TBI). The current objective is to explore multi-Watt NILT efficacy in a proof-of-concept study as a treatment for depression. Methods: Thirty-nine sequential patients treated for TBI between March 2013 and May 2017 provided depression self-assessment data and/or were administered the Hamilton Depression Rating Scale. Each completed the Quick Inventory of Depression Symptomatology-Self Reports (QIDS) before and after treatment. Patients received multi-Watt NILT using near-infrared lasers (810/980 nm at 8-15 Watts) applied to forehead and temporal regions bilaterally for 9-12 minutes to each area. Pre- and post-treatment scores were analyzed by paired t-tests. Results: All met QIDS criteria for mild to severe depression and 69% had prior antidepressant trials. For 36 of the 39 patients, after 16.82 + 6.26 treatments, QIDS scores indicated a robust response (decrease of QIDS total score by > 50%). For 32 of 39 patients post-treatment QIDS scores indicated a remission from depression (decrease of QIDS total score < 5). Overall, the QIDS score fell from 14.10 + 3.39 to 3.41 + 3.30 SD (p = 6.29 X 10-19). With 12 or fewer treatments, QIDS score dropped from 14.83 + 2.55 to 4.17 + 3.93. Patients receiving 13 or more treatments showed a change in QIDS score from 13.67 + 3.64 to 3.11 + 3.14. Those (N = 15) who received the entire treatment course within 8 weeks or less (5.33 + 1.72 weeks) showed a change in QIDS score from 13.86 + 3.14 to 4.5 + 3.94. Suicidal ideation resolved in all, but two patients. Patients remained in remission for up to 55 months after a single course of treatment. Conclusion: This is the first report of high-powered NILT showing efficacy for depression. Patients saw benefit often within 4 treatments and resolution of depressive symptoms occurred within 4 weeks for some. These data raise an intriguing possibility – that NILT may be a safe, effective, and rapid treatment for depression comorbid with TBI and possibly primary MDD. A double-blind, placebo controlled trial is warranted to verify these proof-of-concept data.